Complete sequence and genomic annotation of carrot torradovirus 1 - Rozado-Aguirre, Zuriñe; Adams, Ian; Fox, Adrian; Dickinson, Matthew; Boonham, Neil (Springer, 2017)
Carrot torradovirus 1 (CaTV1) is a new member of the genus Torradovirus within the family Secoviridae. CaTV1 genome sequences were obtained from a previous next-generation sequencing (NGS) study and were compared to other members and tentative new members of the genus. The virus has a bipartite genome, and RACE was used to amplify and sequence each end of RNA1 and RNA2. As a result, RNA1 and RNA2 are estimated to contain 6944 and 4995 nucleotides, respectively, with RNA1 encoding the proteins involved in virus replication, and RNA2 encoding the encapsidation and movement proteins. Sequence comparisons showed that CaTV1 clustered within the non-tomato-infecting torradoviruses and is most similar to motherwort yellow mottle virus (MYMoV). The nucleotide sequence identities of the Pro-Pol and coat protein regions were below the criteria established by the ICTV for demarcating species, confirming that CaTV1 should be classified as a member of a new species within the genus Torradovirus.